Foldable Bed Design Concept for COVID-19 Patient: A Machine Design Case Study - Laely Muryanti; Laela Nur Fitria; Glenn Hanaya; Farid Triawan (Universitas Pendidikan Indonesia (UPI), 2021)
Coronavirus disease 2019 (COVID-19) has become a serious problem around the world. The pandemic has given several bad impacts, especially in the medical operation. Hospitals are facing problems in which they are lacking the patient bed facility. The objective of this paper is to propose an adjustable medical bed that can be folded as a chair for COVID-19 patients. This foldable bed is employing the hydraulic system as the lifting mechanism. It can raise up from 0.62 to 1 meter height and withstand loads up to 400 kg. Other supporting features and mechanisms will be explained in this paper. Furthermore, the theoretical strength analyses of this proposed design are conducted under the static and fatigue loading. In the static analysis, the safety factor due to the normal and shear stress is 7.5 based on the Maximum Shear Stress failure criterion theorem. Meanwhile, in the fatigue analysis, the safety factor based on the Modified Goodman and ASME-Eliptic criteria are 3.6 and 3.9, respectively. The infinite life of this design is predicted. In addition, this paper is expected to be used as a reference for developing a more reliable design for COVID-19 patients due to lack of bed facilities.